Large-scale investigation of single cell activities and response dynamics in a microarray chip with a microfluidics-fabricated microporous membrane. Issue 13 (9th June 2021) - Han, Kai; Sun, Meilin; Zhang, Jinwei; Fu, Wenzhu; Hu, Rui; Liu, Dan; Liu, Wenming
Abstract : We present a parallel, large-scale, and versatile investigation of the single cell activity and response dynamics in a facile assembled microwell array chip with a microfluidics-molded microporous membrane. Abstract : Microengineering technology involving microfabrication, micropatterning and microfluidics enables promising advances in single cell manipulation and analysis. Herein, we describe a parallel, large-scale, and temporal investigation of diverse single cell activities and response dynamics using a facile-assembled microwell array chip with a microfluidics-molded microporous membrane. We demonstrated that the versatility with respect to geometrical homogeneity and diversity of microporous membrane fabrication, as well as the stability, repeatability, and reproducibility rely on the well-improved molding. Serial and practical operations including controllable single cell trapping, array-like culture or chemical stimulation, and temporal monitoring can be smoothly completed in the chip. We confirmed that the microwell array chip allowed an efficient construction of a single cell array. Using the cell array, on-chip detection of single cell behaviours under various culture and drug therapy conditions to explore phenotypic heterogeneity was achieved in massive and dynamic manners. These achievements provide a facile and reliable methodology for fabricating microporous membranes with precise control and for developing universal microplatforms to perform robust manipulation and versatile analysis of single cells. This work also offers an insight into the development of easy to fabricate/use and market-oriented microsystems for single cell research, pharmaceutical development, and high-throughput screening.